2019
DOI: 10.15252/embj.201899266
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal degradation within endocytic organelles mediates antigen cross‐presentation

Abstract: During MHC‐I‐restricted antigen processing, peptides generated by cytosolic proteasomes are translocated by the transporter associated with antigen processing (TAP) into the endoplasmic reticulum, where they bind to newly synthesized MHC‐I molecules. Dendritic cells and other cell types can also generate MHC‐I complexes with peptides derived from internalized proteins, a process called cross‐presentation. Here, we show that active proteasomes within cross‐presenting cell phagosomes can generate these peptides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 57 publications
3
39
0
1
Order By: Relevance
“…The same study also reported an ubiquitination preceding proteaphagy, a mechanism that is probably common to both pathways as Besche and colleagues 27 showed enhanced an alternative route to the lysosomes via endosomes is possible, since it was just reported that active proteasomes can be internalized to endosomes/phagosomes to mediate antigen cross-presentation but do not stay there permanently 43 .…”
Section: Discussionmentioning
confidence: 75%
“…The same study also reported an ubiquitination preceding proteaphagy, a mechanism that is probably common to both pathways as Besche and colleagues 27 showed enhanced an alternative route to the lysosomes via endosomes is possible, since it was just reported that active proteasomes can be internalized to endosomes/phagosomes to mediate antigen cross-presentation but do not stay there permanently 43 .…”
Section: Discussionmentioning
confidence: 75%
“…Recruitment of the NOX2, whose activity is crucial to regulate the levels of phagosomal proteolysis required for optimal cross-presentation(75), is mediated by both VAMP8and SNAP-23(32,76). Our finding that absence of VAMP3 increases the level of crosspresentation by L. amazonensis-harboring communal PVs illustrates the complex regulation of this process and indicates that communal PVs do not behave like model phagosomes used to define the molecular bases of cross-presentation(20,22,77). Further characterization of communal PVs induced by L. amazonensis and of the role of VAMP3 in their formation may therefore yield novel information on the process of antigen cross-presentation in the context of cells infected with a pathogen residing in communal vacuoles.We provided evidence that both VAMP3 and VAMP8 participates in the development and functionality of L. amazonensis-harboring communal PVs.…”
mentioning
confidence: 87%
“…Cross-presentation of microbial peptides on major histocompatibility (MHC) I molecules is an important host defense mechanism aimed at deploying CD8 + T cells responses against intracellular pathogens, including Leishmania (67)(68)(69)(70)(71)(72)(73). Previous studies revealed that phagosomes acquire, through a series of interactions with other organelles, the machinery required to become self-sufficient for antigen cross-presentation (20)(21)(22). However, the involvement of the various vesicular trafficking pathways in this process remains to be fully understood (72,74).…”
Section: Vamp3 Negatively Regulates Antigen Cross-presentationmentioning
confidence: 99%
“…Sengupta et al () introduce a surprising new concept stating that proteasomes are present in the lumen of endocytic and phagocytic organelles. They used immunoelectron, confocal, and time‐lapse microscopy, to confirm the presence of multiple subunits of the proteasome in the lumen of endosomes and phagosomes.…”
Section: Models For the Location Of The Proteasome In Cross‐presentationmentioning
confidence: 99%
“…One of the main criticisms for such an integrated pathway is based on the fact that cross‐presentation is inefficient in cells lacking the TAP transporters, suggesting that processing has to occur in the cytoplasm prior to loading in the ER or phagosome lumen (see pathways 1 and 2 in Fig ). The study of Sengupta et al () addresses this issue by showing that one of the consequences of knocking‐out TAP1 is to decrease the availability of MHC I and its binding partner β2‐microglobulin. In this context, expressing β2‐microglobulin in bone marrow‐derived dendritic cells lacking TAP1 −/− increased the cross‐presentation of phagocytosed ovalbumin.…”
Section: Models For the Location Of The Proteasome In Cross‐presentationmentioning
confidence: 99%